PELAKSANAAN PENGAWASAN PEGAWAI PADA UNIT PELAYANAN LALU LINTAS DAN ANGKUTAN WILAYAH I PROVINSI KALIMANTAN BARAT - E.21110007, Hosnawati (FISIP Universitas Tanjungpura, 2014)
The journal is published from the thesis entitled Implementation Monitoring Employee Services Unit Traffic and Transportation, Region I Office of Transportation, Communication and Information Technology of West Kalimantan Province. The problems discussed in this paper is about Setting the Standard in Financing services, Quality Products, Quality Process. The purpose of this study is to describe the implementation of Internal and External Supervision Service Unit Employees In Traffic and Transportation, Region I Office of Transportation, Communication and Information Technology of West Kalimantan Province. The results showed that the process of Setting the Standard in the Service Unit of Traffic and Transportation, Region I care financing in the Service Unit Traffic and Transportation, Region I has not been effective. This is due to the availability of funds and facilities are extremely minimal or inadequate, temporary work programs that are made affect the duties and functions, then nothing should be done in accordance with existing facilities. In addition there are cases of extortion done by weighing the operational staff. On product quality Services Unit Traffic and Transportation Region I is still not optimal, this is because there are some employees who transfer employees. Furthermore, for monitoring the performance of employees in the field of operational confirm their attendance to measure the performance of employees. It aims to prevent and minimize the occurrence of errors made by employees in the field of operations directly in the field. In addition, the implementation of the program of work done that was made in the early years were divided into 4 (four), the work program is to be a benchmark of the performance UPLLA region I. From the quality of the processes in the Service Unit of Traffic and Transportation, Region I is considered not optimal, it is because that still required the installation of CCTV at weigh stations, so that employees in the field are not contrary. Furthermore, in the field of Traffic Services Unit and Transport to give warning to the officers who do not obey the rules. As well as counseling and guidance to employees on the ground that there is no play between officers with the owner of goods transport vehicle. This is done so that the employees in the field in carrying out supervisory duties in accordance with the rules of work.Â Keywords: Setting the Standard, Financing Services, Quality Products, Quality Process.